Genomic and Long-Term Transcriptomic Imprints Related to the Daptomycin Mechanism of Action Occurring in Daptomycin- and Methicillin-Resistant Staphylococcus aureus Under Daptomycin Exposure - Cafiso, Viviana; Stracquadanio, Stefano; Lo Verde, Flavia; De Guidi, Irene; Zega, Alessandra; Pigola, Giuseppe; Stefani, Stefania (Frontiers in Microbiology, 2020)
Daptomycin (DAP) is one of the last-resort treatments for heterogeneous Vancomycin-Intermediate Staphylococcus aureus (hVISA) and Vancomycin-Intermediate S.aureus (VISA) infections. DAP-resistance (DAP-R) is multifactorial and mainly related to cell-envelope modifications caused by Single Nucleotide Polymorphisms and/or modulation mechanisms of transcription emerging as result of a self-defense process in response to DAP-exposure. Nevertheless, the role of these adaptations remains unclear. We aim to investigate the comparative genomics and late post-exponential growth-phase transcriptomics of two DAP-Resistant/DAP-Susceptible (DAPR/S) MRSA clinical strain-pairs to focalize the genomic, the long-term transcriptomic fingerprinting and adaptations related to the DAP mechanism of action acquired in-vivo under DAP-pressure using Illumina Whole-Genome Sequencing (WGS), RNA-seq, bioinformatics, and real time qPCR validation. Comparative genomics revealed that membrane protein and transcriptional regulator coding-genes emerged as shared functional coding-gene clusters harboring mutational events related to the DAP-R onset in a strain-dependent manner. Pairwise transcriptomic enrichment analysis highlighted common and strain-pair dependent KEGG-pathways, whilst DAPR/S double-pair cross-filtering returned 53 differentially expressed genes (DEGs). A multifactorial long-term transcriptomic-network characterized DAPRMRSA, including alterations in: i) peptidoglycan biosynthesis, cell division and cell-membrane (CM) organization genes, as well as a cidB/lytS autolysin genes; ii) ldh2 involved in fermentative metabolism; iii) CM-potential perturbation genes; iv) oxidative and heat/cold stress-response related genes. Moreover, a d-alanyl-d-alanine decrease in cell-wall muropeptide characterized DAP/Glycopeptide cross-reduced susceptibility mechanisms in DAPR MRSA. Our data provide a snapshot of DAPR MRSA genomic and long-term transcriptome signatures related to the DAP-MOA evidencing that a complex network of genomic changes and transcriptomic adaptations are required to acquire DAP resistance.